A controllable interlayer shielding effect in twisted multilayer graphene quantum dots - Wang, Xian (2024)
When multilayer graphene (MLG) is subjected to a vertical electric field, electrons traverse across the layers and its interlayer electrical conductance and shielding effect exhibit remarkable diversity, leading to exotic phenomena and diverse applications in photoelectric devices. The rearrangement of electrons induced by this external field is aptly described by polarizability, which quantifies the electronic response to the applied field. In this work, we have developed a polarizability decomposition scheme based on field-induced electron density variations computed using a first-principles approach. This scheme allows us to isolate the inter- and intra-layer contributions from the total polarizability of twisted multilayer graphene (TMG) quantum dots. The inter- and intra-layer counterparts reflect the charge transfer (CT) and field shielding effects among the layers, respectively. While the strongest shield effect is observed between the outermost two layers, the largest CT change is noted in the outermost layers, but small or nearly zero CT changes in the inner layers. Significant CT and shielding effects are observed not only in strongly coupled Bernal stacking, but also in the structures misaligned from full-(AA)N stacking by a small and size-dependent twist angle. The dielectric behaviors of the TMG quantum dots of a few layers are layer-dependent and different from those of typical dielectrics. Moreover, both the shielding and CT effects exhibit variation with thickness, twist angle and disc size, suggesting controllable conductive/dielectric conversion in the vertical direction. Considering the inter- and intralayer polarizability, our study addresses the precise modulation of interlayer conductance and shielding effect for TMG quantum dots, essential for microstructure design and performance manipulation of MLG-based photoelectric devices.